A new species of Forcipomyia (Microhelea) Meigen (Insecta: Diptera: Ceratopogonidae) from the Neotropical region - Falaschi, Rafaela Lopes; Albertoni, Fabiano Fabian; Maria Fusari, Lívia (Zootaxa, 2014)
We describe and illustrate a new species of biting midge belonging to the subgenus Forcipomyia (Microhelea), from the Estação Biológica de Boracéia, São Paulo State, Brazil. We include illustrations of the mouthparts, head, thorax, legs, abdominal setae, and habitus. The new species is similar to the few other recorded Neotropical species of biting midges, such as Forcipomyia (Microhelea) alleni, Forcipomyia (Microhelea) castneri, Forcipomyia (Microhelea) grandcolasi, and Forcipomyia (Microhelea) tettigonaris. However, it can be distinguished by the combination of external characters, such as the number of plates on the maxilla, the number of denticles on the mandible, the size of the labellum, and the morphology of the palpus. The two female specimens examined were found biting on a female stick bug, Paraphasma paulense (Phasmida: Pseudophasmatidae), which was attracted to a light trap.